Phytochemical constituents, antioxidant and antibacterial activities of Plectocephalus varians (A. Rich.) C. Jeffrey ex Cufod root extracts - Melaku Birhane Gashaye; Yihenew Simegniew Birhan (BMC, 2023)
Abstract Plants have been used to treat diverse types of diseases in different cultural groups around the globe. In this regard, the root of Plectocephalus varians (P. varians) is claimed to have a beneficiary effect in treating cancer and hemorrhoids in Ethiopia. Hence, this study aimed at the phytochemical investigation, antioxidant, and antibacterial activities of n-hexane, acetone, and methanolic extracts of P. varians root. The different crude extracts of P. varians were obtained through maceration technique. The total phenolic content (TPC) and total flavonoid contents (TFC) of the extracts were estimated using Folin-Ciocalteu Reagent (FCR) and aluminum chloride colorimetric assays, respectively. The antioxidant activities of the extracts were determined by 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging and ferric reducing antioxidant power (FRAP) assays. The antibacterial activities of the extracts were assessed by using disc diffusion method. The results echoed the presence of alkaloids, saponins, flavonoids, steroids, phenols, tannins, anthraquinones, terpenoids, polyphenols, and glycosides in the root of P. varians. The methanolic root extract (MRE) had the highest TPC (107.18 mg GAE/g) and TFC (120.194 mg QE/g) followed by acetone root extract (ARE) (TPC = 98.68 mg GAE/g; TFC = 64.038 mg QE/g) and n-hexane root extract (HRE) (TPC = 12.39 mg GAE/g; TFC = 9.917 mg QE/g). The DPPH radical scavenging and FRAP assays demonstrated the antioxidant effects of HRE (IC50 = 681.75 ppm; EC50 = 60.65 ppm), ARE (IC50 = 165.73 ppm; EC50 = 51.67 ppm) and MRE (IC50 = 132.06 ppm; EC50 = 30.97 ppm) of P. varians. Furthermore, the root fractions elicited pronounced dose-dependent growth inhibition against Staphylococcus aureus, Streptococci pyogenes, Escherichia coli, and Klebsiella pneumoniae with mean zone of inhibition (MZI) ranging from 11 ± 0.38 to 20 ± 0.04 mm at 800 ppm. Overall, the present study provides ethnopharmacological evidence suggesting the medicinal importance of P. varians. The results also call for further bioassay-guided phytochemical screening and in vitro and/or in vivo bioactivity testing.